Single-phase Flyback Photovoltaic Micro-inverter Grid-connected Control Strategy with a Lag-time Compensation Technique - MA Chen cheng; YU Feng; WU Xiao xin; MAO Jing feng (Journal of Harbin University of Science and Technology, 2023)
In terms of the single-phase flyback photovoltaic micro-inverters, the traditional discontinuous current mode algorithm takes the disadvantages of large phase delay between the grid-connected current and voltage, and high harmonics of grid-connected current. Therefore, this paper proposes a grid-connected control strategy with a lag-time compensation technique for the single-phase flyback inverter. First, the small signal model of the system is established to obtain the two components in the grid-connected current model, namely, steady-state quantity and transient quantity. Out of them, the steady-state quantity is responsible for calculating the steady-state duty cycle, while the transient quantity is for the transient duty cycle. The final duty cycle applied to the inverter is the superposition of the two duty cycles. Thereafter, in order to compensate the lag-time problem of control signal owing to the data acquisition and numerical calculation, a weighted transfer function is designed to minimize the phase difference between the output grid- connected current and the grid voltage, thus ensuring the high stability of the single-phase flyback micro-inverter. Finally, the tests based on the 150 W experimental prototype verify the effectiveness of the proposed method.